Medical tourism from the UK to Poland: how the market masks migration. Issue 20 (15th December 2020) - Horsfall, Daniel
ABSTRACT: Much medical travel happens, but it is misleading to label it as 'medical tourism'. Rather, patterns of travel reflect a range of drivers: from longstanding cultural, economic and political ties to the country providing treatment, to word-of-mouth networks. Poland provides a particularly interesting case, as it has been touted as the leading medical tourism destination for UK medical travellers in Europe; marketing by Polish providers is advanced and there is strong government support for the industry. In this paper examining data from the UK's International Passenger Survey for the past 15 years, we demonstrate that, while travel to Poland has indeed increased dramatically, much of this actually reflects a wider pattern of Polish migrants living in the UK and returning to Poland for medical care rather than increased 'medical tourism' consumer activity by Britons in Poland.